2023
DOI: 10.1039/d3py00550j
|View full text |Cite
|
Sign up to set email alerts
|

ROPISA of salicylic acidO-carboxyanhydride: fast polymerization followed byin situkinetics-driven self-assembly

Abstract: Polymerization-induced self-assembly (PISA) has become a significant technique for creating well-defined block copolymer nanoparticles. However, achieving biocompatible and degradable nanoparticles using one-pot scalable chemistry through PISA is rarely reported due...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…As expected, variation of the NaOH concentration could be used to vary mass loss in all species, which indicates that the degradation mechanism is purely hydrolytic (Figure , SI Figure 24). Most importantly, by these degradation studies we confirmed the release of salicylic acid derivatives in all cases through spectroscopy, with more prolonged release demonstrated by our materials compared with other PolyAspirins and encapsulated/incorporated forms of salicylic acid. ,, ,, The degradation also follows a surface erosion process, as confirmed through optical observations of film erosion (SI Figure 25) as well as of porous structures over time as well as through more complex drug release studies. Through selection of the linker species, the daily released concentration could be varied while maintaining linear release profiles over time.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…As expected, variation of the NaOH concentration could be used to vary mass loss in all species, which indicates that the degradation mechanism is purely hydrolytic (Figure , SI Figure 24). Most importantly, by these degradation studies we confirmed the release of salicylic acid derivatives in all cases through spectroscopy, with more prolonged release demonstrated by our materials compared with other PolyAspirins and encapsulated/incorporated forms of salicylic acid. ,, ,, The degradation also follows a surface erosion process, as confirmed through optical observations of film erosion (SI Figure 25) as well as of porous structures over time as well as through more complex drug release studies. Through selection of the linker species, the daily released concentration could be varied while maintaining linear release profiles over time.…”
Section: Resultssupporting
confidence: 73%
“…59 Yao et al used the cyclic salicylic acid monomers for polymerization induced self-assembly of nanostructures. 60 Such limitation is by no means only found with these PolyAspirins and in fact is a significant problem in medical technology where conventional manufacturing may not be able to achieve devices and surface features best suited for material-tissue integration or performance. 4 For this reason, materials which may be processed using additive manufacturing techniques offer exciting opportunities in clinical science, with stereolithography (SLA) and digital light processing (DLP) producing scaffolds with excellent surface feature resolution and reproducibility.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three similar monomers, namely, SAOCA, 5-MeSAOCA, and 4-FSAOCA, exhibiting variations in chemical activities due to the electron-donating or withdrawing effect of the substituent group on the benzene ring, were employed to explore the feasibility of sequential copolymerization from the mixed SAOCA-series monomers. As previously reported, , these monomers were observed to undergo polymerization-induced self-assembly at suitable concentrations in tetrahydrofuran (THF) due to the transition of solvophilic monomers to solvophobic polymer during polymerization. Consequently, in this study, the monomer concentration was maintained below 0.05 M to ensure a smooth progression of homogeneous polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we developed a one pot scalable synthesis for polyester-based block copolymer nanostructures coined Ring-Opening Polymerization-Induced Crystallization-Driven Self Assembly (ROPI-CDSA), 14,21 one of the earliest examples of PISA for ring-opening polymerization (ROPISA). 12,15,22–27 To date, ROPISA has applied to core-forming polymers derived from N -caroxyanhydrides, 12,22,26 l -lactide, 14,21 salicylic acid o-carboxyanhydrides, 15,23 carbonates, 27 and lactones, 24 with the processes using l -lactide, carbonates, and lactones containing a semicrystalline core. In our example of ROPI-CDSA, polyethylene glycol is chain extended with l -lactide using organocatalysts in toluene, a selective solvent to form poly( l )-lactide- b -polyethylene glycol (PLLA- b -PEG).…”
Section: Introductionmentioning
confidence: 99%